Sustainable Development Education in International Higher Education: A Bibliometric analysis - Du, Yan; Jiang, Bo; Wang, Shaojie; Shen, Xingzhu (Quality in Sport, 2025)
The importance of sustainable development is increasingly recognized, prompting universities to strive toward achieving the Sustainable Development Goals (SDGs). This review focuses on the meticulous collection and analysis of relevant papers within the context of sustainable development education, followed by the organization and consolidation of these findings into distinct sustainable domains using the PRISMA methodology. A total of 77 existing articles and publications retrieved from the Web of Science database were utilized to conduct an in-depth exploration of current research. This study, based on 77 documents from the Web of Science core database, employs systematic bibliometric analysis to trace the education for sustainable development (ESD) in global universities. Using the PRISMA method, VOSviewer, and Excel tools, research clusters, high-output countries, and major journals were identified. Key findings indicate that research focus has shifted from theoretical exploration to practical innovation, encompassing service-learning, digital tools, and interdisciplinary curriculum integration. Core challenges include fragmented ESD implementation, insufficient sustainability assessment, and unequal resource allocation. This study proposes action strategies: embedding the Sustainable Development Goals (SDGs) into disciplinary frameworks, strengthening teacher training programs, and leveraging artificial intelligence to develop scalable solutions. This analysis provides a roadmap for policymakers, educators, and institutions to enhance ESD effectiveness and university sustainability.